ANALISIS TERMINOLOGI PENDIDIK DAN PESERTA DIDIK DALAM AL-QUR’AN - Sayuti Hamdani; Ahmad Zain Sarnoto; Samsuri Samsuri (Hikmah: Journal of Islamic Studies, 2024)
AbstractThis article aims to analyze the terms in the Qur'an related to educators and students. With the literature study method used in this study, it was revealed that educational and learning activities are essentially an interaction between educators and students; educators are the party that conveys knowledge, experience and values, while students are the party who seeks and receives that knowledge, experience and values. A number of signs must be maintained in the interaction process, so that education and learning activities are well created. Students in this context are not only as objects, but subjects of education. The Qur'an as a guide for human life regulates life from various aspects ranging from social, economic, worship, educational aspects and so on. In the aspect of education, the Qur'an emphasizes the importance of studying and the degree of knowledgeable people, educational objectives, teaching methods, to the importance of students in the world of education. Education is guidance carried out by an adult to the educated in growth so that he has personality which is Islamic. Students formally are people who are in the phase of growth and development both physically and psychologically, growth and development are characteristics of students who need guidance from an educator. In this case, educators have an important role for the continuity of education, whether or not educators have a major influence on educational outcomes for students who are the most important objects in education. AbstrakArtikel ini bertujuan untuk menganalisis istilah-istilah dalam al-Qur’an yang terkait dengan pendidik dan peserta didik. Dengan metode studi pustaka yang digunakan dalam penelitian ini terungkap bahwa aktivitas pendidikan dan pembelajaran hakikatnya merupakan interaksi antara pendidik dan peserta didik; pendidik sebagai pihak yang menyampaikan pengetahuan, pengalaman dan nilai, sedangkan peserta didik pihak yang mencari dan menerima pengetahuan, pengalaman dan nilai itu. Sejumlah rambu-rambu harus dipelihara dalam proses interaksi tersebut, sehingga aktivitas pendidikan dan pembelajaran tercipta dengan baik. Peserta didik dalam konteks ini bukan hanya sebagai objek, tetapi subjek pendidikan. Al-Qur’an  sebagai pedoman hidup manusia mengatur kehidupan dari berbagai aspek mulai dari aspek sosial, ekonomi, ibadah, pendidikan dan lain sebagainya. Dalam aspek pendidikan, al-Qur’an menegaskan tentang pentingnya menuntut ilmu, Tingginya derajat orang yang berilmu, tujuan pendidikan, metode pengajaran, sampai dengan pentingnya peserta didik dalam dunia pendidikan.Pendidikan merupakan bimbingan yang dilakukan oleh seorang dewasa kepada terdidik dalam masa pertumbuhan agar ia memiliki kepribadian yang Islami. Peserta didik secara formal adalah orang yang sedang berada pada fase pertumbuhan dan perkembangan baik secara fisik maupun psikis, pertumbuhan dan perkembangan merupakan ciri dari peserta didik yang perlu bimbingan dari seorang pendidik. Dalam hal ini pendidik mempunyai peranan penting untuk berlangsungnya pendidikan, baik atau tidaknya pendidik berpengaruh besar terhadap hasil pendidikan bagi peserta didik yang merupakan obyek terpenting dalam pendidikan.